1964
DOI: 10.1104/pp.39.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Growth Retardant CCC on Floral Initiation and Growth in Pharbitis nil

Abstract: Growth-retarding chemicals such as Amo-1618 (2,12 ), CCC [(2-chloroethyl No specific effects of growth retardants on floral initiation in short-day plants (SDP) have heretofore been reported. The present paper concerns the effects of the growth retardant CCC on flower formation and growth of the SDP Pharbitis nil and the rev-ersibility of these effects by gibberellin A3. Materials and MethodsSeeds of Pharbitis nil Chois., strain Violet, were treated with concentrated sulfuric acid for 60 minutes ancl subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0
1

Year Published

1965
1965
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 16 publications
3
22
0
1
Order By: Relevance
“…For example, they strongly support the conclusion that these gibberellins play a part in the regulation of flower formation (1,17,18), of sex expression in cucumbers (10) Ho-wever, in the barley-endosperm system B-995 was quite ineffective in modifying the GA-induced response (12). Further experiments on the action mechanism of B-995 and related compounds are clearly needed.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…For example, they strongly support the conclusion that these gibberellins play a part in the regulation of flower formation (1,17,18), of sex expression in cucumbers (10) Ho-wever, in the barley-endosperm system B-995 was quite ineffective in modifying the GA-induced response (12). Further experiments on the action mechanism of B-995 and related compounds are clearly needed.…”
Section: Discussionmentioning
confidence: 56%
“…The most common response is reduction of stem elongation which in extreme cases can result in almost rosette-like growth habit but which, apart from a deeper-green color and greater thickness of the leaves, is usually not associated with pronounced anomalies of development or structure, as is, for example, growsvth inhibition by high doses of .auxins or related compoun(ls. Another effect, observe(l in some plants, is suppression of the flowerinducing effect of favorable photoperiods (1,17,18). This effect is also selective, vegetative growth, as expressed by the rate of leaf formation, not being affected at all, or affected to a much lesser extent.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Dwarfing agents, such as 2-chloroethyltrimethyl amnmonium chloride (CCC) and (4-hvdroxy-5-isopropyl-2-methylphenyl) trimethyl ammonium chloride-i-piperidine carboxvlate (AMO-1618), which inhibit gibberellin production, have been useful in studying the role of endogenous gibberellins in flowering of a long-day plant (2), of a .short-day plant (15), of a long-short-dav plant (17), and of plants requiring low temperature for flower formation (8,13 The plants that remained vegetative formed a rosette after GA treatment was terminated, when a total of 300 yg had been applied per plant. (fig 2).…”
mentioning
confidence: 99%
“…Zeevart (14) has shown that 2-chloroethyltrimethylammonium chloride (CCC), an inhibitor of gibberellin biosynthesis, blocks photoperiodically indtuced flowering in the short-day planit, Phlrbitis nil. Since this inhibition wvas completely reversed by application of gibberellic acid (GA.:), it appears that gibberellins are involved at some stage of the flower induction process in this plant.…”
mentioning
confidence: 99%